CADASTRAL WORKS CARRIED OUT IN ORDER TO REGISTER IN THE INTEGRATED LAND BOOK SYSTEM SOME STREETS LOCATED IN THE VILLAGE OF ŞUGAG TO CERTIFY THE OWNERSHIP RIGHT (PANGEEA, 2025)
The present paper aims at the inclusion in the integrated land book system of some streets located in the village of Şugag, in order to issue a Government Decision for the attestation of the right of ownership.
Keywords: land book system; attestation of the right of ownership; delimitation plan